2021
DOI: 10.1136/bmjpo-2021-001078
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre service evaluation of presentation of newly diagnosed cancers and type 1 diabetes in children in the UK during the COVID-19 pandemic

Abstract: BackgroundThe COVID-19 pandemic led to changes in patterns of presentation to emergency departments. Child health professionals were concerned that this could contribute to the delayed diagnosis of life-threatening conditions, including childhood cancer (CC) and type 1 diabetes (T1DM). Our multicentre, UK-based service evaluation assessed diagnostic intervals and disease severity for these conditions.MethodsWe collected presentation route, timing and disease severity for children with newly diagnosed CC in thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Any delay in diagnosing life-threatening childhood diseases such as complicated diabetes with severe DKA must be seen as a wake-up call for national health systems. In a recent study (16), there was no evidence of a delay in the diagnosis or increased disease severity for cancers or type 1 diabetes during the first wave of the COVID-19 pandemic in centers in the UK. Therefore, any delays in diagnosing diabetes are heterogeneous according to individual contexts and geography.…”
Section: Possible Causes Of Increased Dka and The Role Of Socioeconom...mentioning
confidence: 91%
“…Any delay in diagnosing life-threatening childhood diseases such as complicated diabetes with severe DKA must be seen as a wake-up call for national health systems. In a recent study (16), there was no evidence of a delay in the diagnosis or increased disease severity for cancers or type 1 diabetes during the first wave of the COVID-19 pandemic in centers in the UK. Therefore, any delays in diagnosing diabetes are heterogeneous according to individual contexts and geography.…”
Section: Possible Causes Of Increased Dka and The Role Of Socioeconom...mentioning
confidence: 91%
“…Surprisingly, compared to the same period in 2019, the results in 2020 showed a reduction of approximately 20% in new diabetes cases. Similar situations were noticed both in India and the UK [47,48]. A possible explanation would be that along with the lockdown, children were less exposed to seasonal viruses, which are known to be triggers for new-onset type 1 diabetes cases [49,50].…”
Section: T1dm and Covid-19mentioning
confidence: 52%
“…However, studies have found no significant impact on route to diagnosis and severity of presentation for type 1 diabetes and new diagnosed cancers, as well as no impact on overall outcomes for asthma, pyloric stenosis and appendicitis. [10][11][12][13][14] There have also been concerns that some CYP were unable to access specialist services in hospitals. For example, a study of radiology outpatient activity at a tertiary children's hospital from March 2020 to March 2021 showed a reduction of 27.3%.…”
Section: Introductionmentioning
confidence: 99%